Three new peacock spiders from Southwestern Australia (Araneae: Salticidae: Euophryini: Maratus Karsch, 1878) - Schubert, Joseph (Zootaxa, 2019)
Three new species of the peacock spider genus Maratus Karsch, 1878 are described from the vicinity of Lake Jasper and Mount Romance in the Southwestern Australia ecoregion: M. aquilus sp. nov., M. combustus sp. nov., M. felinus sp. nov.